2023
DOI: 10.1177/03000605231182547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin and rosuvastatin on dysfunctional coronary circulation in patients with ST-segment elevation myocardial infarction

Abstract: Objective Evidence of therapy for dysfunctional coronary circulation in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI) is limited. This study was performed to compare the effects of atorvastatin and rosuvastatin on dysfunctional coronary circulation. Methods This retrospective study enrolled 597 consecutive patients with STEMI who underwent pPCI in 3 centers from June 2016 to December 2019. Dysfunctional coronary circulation was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In addition, our data suggested that statin use was lower in the NR group than in the reflow group, and statins may reduce the incidence of NR. This result is consistent with the conclusion of Zhou et al [ 29 ]. Although the mechanism for this is not fully understood, it may result from improved endothelial function, inhibition of thrombogenic function, improved stability of atherosclerotic plaques, and reduced oxidative stress and vascular inflammation [ 30 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our data suggested that statin use was lower in the NR group than in the reflow group, and statins may reduce the incidence of NR. This result is consistent with the conclusion of Zhou et al [ 29 ]. Although the mechanism for this is not fully understood, it may result from improved endothelial function, inhibition of thrombogenic function, improved stability of atherosclerotic plaques, and reduced oxidative stress and vascular inflammation [ 30 ].…”
Section: Discussionsupporting
confidence: 94%
“…Statins are the cornerstone of the lipid-lowering treatment and recommended to be administered during the course of STEMI in order to reduce major adverse cardiovascular event rates. 5 Statins have pleiotropic effects and may reduce CIN risk by antioxidant and anti-inflammatory actions. 6 In the present study, 1 the use of statins was not evaluated; it would be better if this was added into the regression analysis.…”
mentioning
confidence: 99%